The application of methodological approach to strategic choice and robustness analysis (Case study: Deciding on product sales promotion and advancement) - Mohammadreza Mehregan; Sahar Jafari; Amir Azara; Shirin Zahedi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This paper examines the application of the strategic choice approach and robustness analysis as a case study on decision-making about product and sales promotion.Methodology: In this research, the strategic choice approach, a research method of soft operations research, is used to analyze, structure, and create decision trees. Also, the robustness analysis technique has been used to select the final scenario accurately. A questionnaire was used to assess each scenario in the decision tree; all employees of a knowledge-based company completed 40 questionnaires. The reliability of the questionnaire was 0.89 with Cronbach's alpha index. Also, these questionnaires were aggregated using the arithmetic mean.Findings: This study presented a combined approach of strategic choice and robustness analysis to structuring and selecting the final scenario in a decision process. The proposed model was implemented in a case study on decision-making regarding a company's sales promotion strategies.Originality/Value: The current research helps structure and quantify decisions while using research techniques in soft operations, such as the strategic choice approach and robustness analysis.